Human Resource Management Practice and Employees’ Retention: A Mediating Effect of Thriving at Work in SMEs - Phumdara, Tawat (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of the study was behind determining the mediating effect of thriving at work in the relationship between HRM practices and employee retention in the context of challenging the SME sector of Indonesia. Design and Method: The study is based on the quantitative design where the preferred mode of data collection was survey based on 376 employees working in the Indonesian SME sector. The study utilised the SEM technique for the purpose of determining the mediation effect of thriving at work in the relationship between HRM practices and employees’ retention. Findings: The findings of the study reveal that in the context of the SME sector of Indonesia, thriving at work partially mediates the relationship between HRM practices and employee retention. Limitation: The study is limited to the SME sector of Indonesia. Meanwhile, the absence of qualitative evidence is also a major limitation of this study.